False, this statement is not true, because if you change the parenthesis, it means that you will do that thing first (PEMDAS)
Therefore, the sstatement is false, because the answers will be completely different,
hope this helps
Answer:
First member-> 1 -> "1 one"
Second member-> 11 -> "2 ones"
Third member-> 21 -> "1 two, 1 one"
Fourth member -> 1211 -> "1ones, 1 two, 2 ones"
Fifth member-> 111221 -> "3 ones, 2 twos, 1 ones"
Sixth member-> 312211 -> "1three, 1 one, 2 twos, 2 ones"
Seventh member-> 13112221 ->" 1 one, 1 three, 2 ones, 3 twos, 1 one"
Step-by-step explanation:
Answer:
y - 1 = 1/2(x -5)
Step-by-step explanation:
I don't know i am right tho so be careful
Let's first turn all the words into numbers:
Two and four tenths = 2.4
One and six tenths = 1.6
Four and one tenth = 4.1
Now lets represent "a number" as x.
Then translate the wording into a linear equation:
![2.4x-3>1.6x-4.1](https://tex.z-dn.net/?f=2.4x-3%3E1.6x-4.1)
Simplify and isolate the variable:
![0.8x>-1.1](https://tex.z-dn.net/?f=0.8x%3E-1.1)
Divide by 0.8
x>1.375 or x>1 3/8
We know that
[volume of a cone]=pi*r²*h/3
h=70 cm
r=15 cm
[volume of a cone]=pi*15²*70/3----------> 16485 cm³
if <span>Cathy uses 500 cm</span>³ of honey----------------> 1 day
<span>16485 cm</span>³--------------------------------------> X
<span>X=16485/500-----------> 32.97 days
the answer is 33 days </span>